Evaluation of landraces of common buckwheat (Fagopyrum esculentum) and indian buckwheat (F. tataricum) for resistance to powdery mildew (Erysiphe polygoni) - KAPOOR, A S; CHAUDHARY, H K (The Indian Journal of Agricultural Sciences, 2013)
Â